Farm-to-table food safety for Colorado produce crops: a web-based approach for promoting good agricultural and handling practices - Wall, Gretchen Lynn, author; Bunning, Marisa, advisor; Kendall, Patricia, committee member; Lamm, Dennis, committee member (Colorado State University. Libraries, 2011)
Fresh fruits and vegetables have been increasingly associated with cases of foodborne illness (CDC, 2010; FDA, 1998). Direct links of these outbreaks to farms highlights the need to employ strategies to reduce pathogenic microbial contamination of fresh produce at this stage of the food system (Bihn & Gravani, 2006). One approach to fresh produce safety on the farm involves participation in voluntary audits based on Good Agricultural Practices (GAPs) and Good Handling Practices (GHPs). Currently, only a small percentage of Colorado producers employ this strategy. In response to new regulations and guidelines, changing food consumption patterns, and improved market access, Colorado producers need to have the flexibility to adopt programs that can help them meet the demands of providing a safer food supply (Rejesus, 2009). In response to these issues, Farm to Table Food Safety for Colorado Producers, a series of three web-based GAPs/GHPs trainings, was developed following the guidelines of FDA, USDA, and the National GAPs program. These trainings were implemented and evaluated targeting small farm producers of fresh fruits and vegetables based on an initial needs assessment to identify potential barriers and drivers for adopting these types of programs. In addition, a series of consumer-friendly, down-loadable fact sheets with nutrition, safe food handling, and recommended storage guidelines was developed to help promote ten selected Colorado specialty crops: apples, berries, broccoli, leafy greens, melons, peaches, peppers, potatoes, squash, and tomatoes. The approach of developing technology-based training modules and educational materials allowed for improved accessibility to growers and produce consumers across the state while accommodating their variable time schedules and need for convenient, reliable information. Pre and post questionnaires were used to measure self-assessed knowledge outcomes along with overall course evaluation items. As a result of participating in the webinar series, producers, buyers, and Extension professionals indicated they planned to utilize the information and resources. Specific topics related to GAPs such as irrigation water quality, management of manure and compost, and food safety legislation were of most interest to the participants and had the most significant increases (p<0.001) in self-reported knowledge, pre to post webinar. The course evaluation showed that produce buyers, Extension professionals, and other webinar attendees intend to utilize the material presented in the webinar series directly or indirectly in their professions, with average mean scores on a 5- point Likert scale (1= Very Unlikely and 5= Very Likely), of 4.2, 4.2, and 3.6, respectively. Overall, reviewers rated the produce fact sheets with a mean score of 4.34 for usefulness (1=Not Useful and 5= Extremely Useful). Feedback gained from the webinar and produce fact sheet evaluations will be a helpful tool in making improvements for future web-based on-farm food safety educational materials.
Keywords: agricultural education; food safety; food safety extension; good agricultural practices; produce safety; webinar